2007
DOI: 10.1073/pnas.0708772104
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Plasmodium falciparum reticulocyte homology protein 4 binds to erythrocytes and blocks invasion

Abstract: Plasmodium falciparum invasion of human erythrocytes involves several parasite and erythrocyte receptors that enable parasite invasion by multiple redundant pathways. A key challenge to the development of effective vaccines that block parasite infection of erythrocytes is identifying the players in these pathways and determining their function. Invasion by the parasite clone, Dd2, requires sialic acid on the erythrocyte surface; Dd2/NM is a variant selected for its ability to invade neuraminidase-treated eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
137
4
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(153 citation statements)
references
References 30 publications
11
137
4
1
Order By: Relevance
“…Because PfRh4 is a key player in phenotypic variation of invasion and sialic acid-independent pathway, we sought to identify its host erythrocyte receptor. We observed that erythroid CR1 is susceptible to trypsin and chymotrypsin treatment, an enzyme profile consistent with that obtained for the abolishment of PfRh4 erythrocyte binding (13,14). Here we show that PfRh4 binds to CR1 on the erythrocyte surface, and that this interaction mediates a functional sialic acid-independent pathway for P. falciparum invasion of human erythrocytes.…”
supporting
confidence: 54%
“…Because PfRh4 is a key player in phenotypic variation of invasion and sialic acid-independent pathway, we sought to identify its host erythrocyte receptor. We observed that erythroid CR1 is susceptible to trypsin and chymotrypsin treatment, an enzyme profile consistent with that obtained for the abolishment of PfRh4 erythrocyte binding (13,14). Here we show that PfRh4 binds to CR1 on the erythrocyte surface, and that this interaction mediates a functional sialic acid-independent pathway for P. falciparum invasion of human erythrocytes.…”
supporting
confidence: 54%
“…falciparum culture (33), BN-PAGE (34), erythrocyte binding assay (35), isolation of viable merozoites (18), immunofluorescence microscopy (36), tritium labeling (22,23), animal immunization, and invasion inhibition assay (37) experiments were done as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…experimental animals to PfRh1, PfRh2, PfRh4, and PfRh5 can inhibit invasion (22,(24)(25)(26)(27). Furthermore, genetic disruption of specific members alters the erythrocyte receptor preference of merozoites during invasion (6,13).…”
mentioning
confidence: 99%